Adopción del rol materno en gestantes multíparas de alto riesgo aplicando el modelo de Ramona Mercer. Hospital General Liborio Panchana Sotomayor. enero-abril 2023 - Chela Chela, Carmen Lucía (2023)
The general objective of the current work is to analyze the adoption of the maternal role in high-risk multiparous pregnant women by applying the Ramona Mercer model at the Liborio Panchana Sotomayor General Hospital during the period January-April 2023. The methodology used in the current work is based on descriptive research, quantitative approach and cross-sectional design, the sample being made up of 30 pregnant women who attend prenatal care over the estimated time, and the technique used was the survey. The results showed that 30% of pregnant women are 20 to 25 weeks pregnant, 80% have preeclampsia and 20% eclampsia, 10% did not plan the pregnancy and 3.3% live alone. Likewise, 43.3% carries less than five prenatal controls, 6.7% have more than four children, 10% feel fear and 6.7% have an average level of confidence for pregnancy care, however, 90.0% of them do not have a positive attitude towards the maternity process. It was concluded that pregnant women with high risk present negative emotions such as fear and lack of confidence to take care of their child, which affects their ability to adopt their mother's role. Keywords: Maternal role, multiparous pregnant women, obstetric risk, Ramona Mercer, adoption of maternal role.